The prognostic implications of a fragmented QRS pattern in patients diagnosed with heart failure - Demirkıran, Ahmet; Yilmaz, Mustafa; Şit, Ömer; Atıcı, Adem; Barman, Hasan (The European Research Journal, 2023)
Objectives: The purpose of this study was to investigate the potential association between the presence of a fragmented QRS (fQRS) pattern on electrocardiogram (ECG) and prognostic outcomes in patients with heart failure (HF). Methods: In the study, 238 patients with a left ventricular ejection fraction of less than 35% were included. The presence of fQRS pattern on ECG was analyzed in all patients. Patients were divided into two groups based on the presence or absence of fQRS on ECG. The primary clinical end points were all-cause mortality and rehospitalization. Results: Baseline demographic characteristics were comparable between the groups. Patients with fQRS had a higher frequency of coronary artery disease and atrial fibrillation (72 (76%) vs 90 (62%), (p = 0.023; 27 (29%) vs 25 (17%), (p = 0.038, respectively). Additionally, patients with fQRS had a higher rate of mortality and rehospitalization during the 5-year follow-up period compared to patients without fQRS. (30 (32%) / 28 (19%), (p = 0.028; 56 (60%) / 50 (35%), p < 0.001, respectively). Multivariable logistic regression analysis revealed that the presence of fQRS was independently associated with mortality and rehospitalization ((p = 0.02 and p < 0.001, respectively). Conclusions: The results of this study suggest that the presence of fQRS on ECG in patients with HF is independently related to a higher risk of mortality and hospitalization. Therefore, the presence of fQRS may be a useful indicator of poor prognosis in these patients.